2023
DOI: 10.3390/medicina59071350
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Smoking Status and Health-Related Physical Fitness and Balance Ability among Older Males in Taiwan

Abstract: The primary aim of this study was to examine the relationships between smoking status and health-related physical fitness and balance ability in older males residing in Taiwan. This investigation adopted a cross-sectional design, utilizing data from 7688 older males who took part in the 2014–2015 wave of the National Physical Fitness Survey of Taiwan. Various data sources, including a standardized structured questionnaire, anthropometric measurements, health-related physical fitness assessments, and balance ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A cross-sectional study involving 7688 elderly Taiwanese males revealed that smoking had a detrimental impact on the cardiopulmonary function, muscular endurance, flexibility, and balance performance of elderly men. Smoking cessation might restore flexibility and static balance performance in the elderly [ 46 ]. In other words, the effects of smoking on risk of fall were reversible.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study involving 7688 elderly Taiwanese males revealed that smoking had a detrimental impact on the cardiopulmonary function, muscular endurance, flexibility, and balance performance of elderly men. Smoking cessation might restore flexibility and static balance performance in the elderly [ 46 ]. In other words, the effects of smoking on risk of fall were reversible.…”
Section: Discussionmentioning
confidence: 99%